DINAMIKA PENGEMBANGAN AMAL USAHA MUHAMMADIYAH BIDANG PENDIDIKAN DI KABUPATEN BANGKA SELATAN: STUDI KUALITATIF - Adelia, Revina; Suyatno; Enung Hasanah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the dynamics of the development of Muhammadiyah charitable enterprises in the field of education in South Bangka Regency and identify factors that support the sustainability of its management. The study used a qualitative approach with a case study method in three educational institutions: Muhammadiyah Elementary School Toboali, Muhammadiyah Junior High School PK Darul Arqom Toboali, and Muhammadiyah Senior High School Toboali. Data were collected through in depth interviews, participatory observation, and documentation studies, then analyzed using an interactive analysis model. The results show that institutional development takes place adaptively and sustainably through different strategies at each level. Muhammadiyah Elementary School Toboali develops following the initiation to stabilization phase according to the school growth model. Muhammadiyah Junior High School PK Darul Arqom Toboali applies the Islamic boarding school model as a differentiation and institutional positioning strategy that strengthens competitiveness. Meanwhile, Muhammadiyah Senior High School Toboali has entered the consolidation phase as a mature institution that focuses on quality stability and reputation management. The decline in the number of students in 2025 is analyzed as a form of managed stabilization, not a decline in performance. This study also found that the internalization of the Muhammadiyah Community Islamic Life Guidelines (PHIWM) serves as cultural capital that influences managerial decisions, shapes organizational culture, and supports the sustainability of the institution at all levels. Value integration, professional management, and program innovation are key factors in maintaining the competitiveness and existence of Muhammadiyah's educational charitable endeavors at the regional level.